1990
DOI: 10.1101/gad.4.7.1149
|View full text |Cite
|
Sign up to set email alerts
|

RNA pseudoknot domain of tobacco mosaic virus can functionally substitute for a poly(A) tail in plant and animal cells.

Abstract: The genomes of many RNA viruses terminate in a tertiary structure similar to the L-conformation of tRNAs and this structure is recognized by many tRNA-specific enzymes such as aminoacyl-tRNA synthetase. Virtually the entire 3'-untranslated region (UTR) of tobacco mosaic virus (TMV) RNA is involved in an extended tertiary structure containing, in addition to a tRNA-like structure, a pseudoknot domain that lies immediately upstream. Although the functions of these structures are not well understood, they are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 49 publications
5
120
3
Order By: Relevance
“…However, studies ofthe IBV frameshift site indicate that an extended simple stem-loop, equal in length to the two quasi-continuous helices in the pseudoknot, cannot replace the pseudoknot without loss of frameshifting efficiency (24). This implies that the pseudoknot has special features, beyond its predicted stability as deduced from base pairing, that may account for its role in frameshifting and other kinds of translational regulation (23,(35)(36)(37)(38)(39).…”
Section: %mentioning
confidence: 99%
“…However, studies ofthe IBV frameshift site indicate that an extended simple stem-loop, equal in length to the two quasi-continuous helices in the pseudoknot, cannot replace the pseudoknot without loss of frameshifting efficiency (24). This implies that the pseudoknot has special features, beyond its predicted stability as deduced from base pairing, that may account for its role in frameshifting and other kinds of translational regulation (23,(35)(36)(37)(38)(39).…”
Section: %mentioning
confidence: 99%
“…However, it has been shown that either deletion of the double-helical segment immediately upstream of the tRNA-like structure or a base substitution that destabilizes the helix results in loss of infectivity. 41) Gallie et al have demonstrated that this pseudoknot region enhances the translation of the genomic RNA, 42) which raises the possibility that the loss of infectivity is caused not only by defects in RNA replication, but also by reduced translation of the TMV-coded proteins. Although the host-encoded eukaryotic elongation factor 1A 43) and p102 (HSP101) 44), 45) have been shown to bind to the pseudoknot region, the importance of the interaction between the pseudoknot region and these proteins in the translation and replication of tobamovirus RNA have not been determined.…”
Section: )mentioning
confidence: 99%
“…The regulated stability of transferrin, granulocyte-macrophage colony-stimulating factor, and histone mRNAs has been shown, at least in part, to be controlled by the binding of specific proteins to consensus sequences in the 3Ј untranslated region (3ЈUTR) of these messages (3, 37, 41). Studies of tobacco mosaic virus, the Drosophila melanogaster developmental gene hunchback, human cytokine, and 15-lipoxygenase mRNAs have demonstrated that the 3ЈUTR also contains information capable of regulating translational efficiency which may be mediated by RNA-binding proteins (13,25,35,36). A major class of RNA-binding proteins which possess an 80-amino-acid consensus element, termed the RNA recognition motif (RRM) (39), which forms the core of a functional RNAbinding domain has been identified.…”
mentioning
confidence: 99%